2020
DOI: 10.1016/j.cell.2020.02.055
|View full text |Cite
|
Sign up to set email alerts
|

Functionally Distinct Neuronal Ensembles within the Memory Engram

Abstract: Highlights d Functionally distinct neuronal ensembles exist within a single memory engram d Fosand Npas4-dependent ensembles undergo distinct synaptic modifications after CFC d Fosand Npas4-dependent ensembles drive memoryguided behaviors in opposite directions d Memory generalization and discrimination, respectively, require MEC and CCK + interneurons

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
165
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(189 citation statements)
references
References 100 publications
12
165
0
1
Order By: Relevance
“…Rare mutations in Nlgn3 have been reported in patients with ID, SCZ and ASDs (Jamain et al, 2003;Parente et al, 2017;Yan et al, 2005). Interestingly, ASD patients show abnormalities in memory discrimination (Beversdorf et al, 2000), which is partly mediated by the activity of hippocampal Cck+ interneurons (Sun et al, 2020;Whissell et al, 2019). This autistic phenotype may be caused by abnormal trans-synaptic interactions of αNrxn1 and Nlgn3 at VGT3+ synapses.…”
Section: Discussionmentioning
confidence: 99%
“…Rare mutations in Nlgn3 have been reported in patients with ID, SCZ and ASDs (Jamain et al, 2003;Parente et al, 2017;Yan et al, 2005). Interestingly, ASD patients show abnormalities in memory discrimination (Beversdorf et al, 2000), which is partly mediated by the activity of hippocampal Cck+ interneurons (Sun et al, 2020;Whissell et al, 2019). This autistic phenotype may be caused by abnormal trans-synaptic interactions of αNrxn1 and Nlgn3 at VGT3+ synapses.…”
Section: Discussionmentioning
confidence: 99%
“…Since TRAP is based on recombination, it would be possible to specifically express genes of interest in the Quinine-TRAPed cells. By combining with Cre-dependent optogenetic/chemogenetic tools, it would be possible to specifically manipulate the activity of TRAPed cells [23,24,28,29,31,32] in the CeA to understand their physiological roles in disgust reactions and conscious disgust [50].…”
Section: Genetic Access To Quinine-activated Neurons In the Ceamentioning
confidence: 99%
“…While the quinine-activated disgust-associated neurons in the IPAC are preferentially accessible by a targeted recombination in active populations (TRAP) method [8,19], it remains unclear whether the accessibility is restricted to the IPAC or not. It is interesting to investigate whether the quinine-activated neurons in the CeA [7] are accessible by TRAP because of the following reasons: (1) the CeA is one of the well-known emotional centers but its role in the disgust reactions remains unclear; (2) the CeA consists of functionally heterogeneous neurons, and the expression of a single molecular marker and Cre transgenics in the molecularly defined neurons likely cannot capture the functional heterogeneity in the CeA [13,20,21]; (3) the CeA neurons are not successfully TRAPed by any stimuli [19,[22][23][24][25][26][27][28][29][30][31][32]; (4) the CeA and the IPAC, where a significant number of neurons were successfully TRAPed by quinine infusion [8], are directly continuous anatomically and are grouped as a part of the distinct anatomical division, the central division of the extended amygdala [9].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent studies have shown that discrete populations of cells contributing to a memory engram have distinct cellular activity, synaptic properties, and behavioral results dependent on the immediate early gene used to identify a given cellular ensemble (Sun et al 2020).…”
mentioning
confidence: 99%
“…Specifically, cFos-mediated engrams have been implicated in promoting memory generalization, such that acute chemogenetic activation of a contextual fear memory led to reduced discrimination between distinct contexts (Sun et al 2020). In parallel, chronic activation of a fear memory in a neutral context may have promoted generalization between the neutral and conditioned context, as evident by decreased freezing in the conditioned context.…”
mentioning
confidence: 99%